The surrogate - Jensen, Louise (Grand Central Publishing, 2018)
Kat and her husband Nick have tried everything to become parents, and are on the point of giving up. Then a chance encounter with Kat's childhood friend Lisa gives Kat and Nick one last chance to achieve their dream. But Kat and Lisa's history hides dark secrets. And there is more to Lisa than meets the eye. As dangerous cracks start to appear in Kat's perfect picture of happily-ever-after, she realizes that she must face her fear of the past to save her family ...